2019
DOI: 10.1002/cctc.201900618
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Role of Water on the Methylation of Hexamethylbenzene in H‐SAPO‐34 from First Principle Molecular Dynamics Simulations

Abstract: The methylation of hexamethylbenzene with methanol is one of the key reactions in the methanol‐to‐olefins hydrocarbon pool reaction cycle taking place over the industrially relevant H‐SAPO‐34 zeolite. This methylation reaction can occur either via a concerted or via a stepwise mechanism, the latter being the preferred pathway at higher temperatures. Herein, we systematically investigate how a complex reaction environment with additional water molecules and higher concentrations of Brønsted acid sites in the ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 128 publications
(350 reference statements)
1
29
0
Order By: Relevance
“…The obtained 2D free energy surface is then projected on to the difference between the two CVs. The phenomenological free-energy barrier is computed by the procedure proposed by Bučko et al ( 57 ) Further details on the methodology and case studies are provided in the work of Bailleul et al ( 58 )…”
Section: Methodsmentioning
confidence: 99%
“…The obtained 2D free energy surface is then projected on to the difference between the two CVs. The phenomenological free-energy barrier is computed by the procedure proposed by Bučko et al ( 57 ) Further details on the methodology and case studies are provided in the work of Bailleul et al ( 58 )…”
Section: Methodsmentioning
confidence: 99%
“…In the small‐pore materials, all the aromatics are retained in the cavities and their maximum size is limited to the cavity size (with tetracyclic aromatics being the largest species found in SAPO‐34 and SAPO‐18 catalysts) [41, 42] . The active species are normally monocyclic aromatics, with hexamethylbenzene being a key active species for SAPO‐34 catalysts, [43] whereas tetramethylbenzenes and pentamethylbenzenes are inferred to be the key active species in SAPO‐18 catalysts [44] . Other studies have revealed that bicyclic aromatics can be active species in SAPO‐34 catalysts at high reaction temperatures [39, 45] .…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, she is further developing research activities to simulate more realistic systems including spatial heterogeneities. She is also an elected member of the Royal (Flemish) Academy for Science and the Arts of Belgium …”
mentioning
confidence: 99%